Blood Warmer Using Peltiers - Park Suksantisakul; Noppadol Maneerat; Thongchan Nakprik; Ruttikorn Varakulsiripunth (My University, 2014)
The purpose of this paper is introduces blood warmer system to easy for anesthesiologists and patients for infusion and facilitate of anesthesiologists work for using blood bag.The system is contained in a rectangular box, inside of which consists of two separate chambers: one housing the electronics inside have; circulating fans, heat sinks, transformer (12v, 100w, 8.3amp) and a PCB with an SG3525 IC for regulation of temperatures in the adjacent chamber and the other the blood warming components inside have is fitted with a shaker, EPDM(Ethylene Propylene Diene Monomer) cushion sheets, a digital thermometer, and two thermo-sensor.Two peltiers and EPDM cushion sheets are employed in the proposed system to quicken the warming of blood bags.Nonetheless, three experiments were conducted with three different blood warming configurations: using one peltier without the EPDM cushion sheets, two peltiers without the EPDM cushion sheets, and two peltiers with the EPDM cushion sheets.The finding indicates that the use of two peltiers together with the plates produces the best results.
Keywords: Thermal Regulation in Medicine